The Composition of Official International Reserves - Martin F.J. Prachowny (Queen's University, Department of Economics, 1969)
The balance of this paper will take the following form: a hypothesis concerning the portfolio manangement of international reserves will be stated; then, this hypothesis will be tested statistically; finally, a discussion of these results and their meaning for the future will conclude the paper.
Keywords: 330